Dimensional stability and water repellent efficiency measurement of chemically modified tropical light hard wood - Md. Saiful, Islam; Sinin, Hamdan; Mohamad, Rusop; Md. Rezaur, Rahman; Abu Saleh, Ahmed; M. A. M., Mohd Idrus (BioResources, 2012)
Chemical modification is an often-followed route to improve physical and mechanical properties of solid wood materials. In this study five kinds of tropical light hardwoods species, namely jelutong (Dyera costulata), terbulan (Endospermum diadenum), batai ( Paraserianthes moluccana), rubberwood (hevea brasiliensis), and pulai ( Alstonia pneumatophora), were chemically modified with benzene diazonium salt to improve their dimensional stability and water repellent efficiency.